x-6=38-12(x+8)

Simple and best practice solution for x-6=38-12(x+8) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x-6=38-12(x+8) equation:



x-6=38-12(x+8)
We move all terms to the left:
x-6-(38-12(x+8))=0
We calculate terms in parentheses: -(38-12(x+8)), so:
38-12(x+8)
determiningTheFunctionDomain -12(x+8)+38
We multiply parentheses
-12x-96+38
We add all the numbers together, and all the variables
-12x-58
Back to the equation:
-(-12x-58)
We get rid of parentheses
x+12x+58-6=0
We add all the numbers together, and all the variables
13x+52=0
We move all terms containing x to the left, all other terms to the right
13x=-52
x=-52/13
x=-4

See similar equations:

| 5x(x+2)=-4 | | -8-5z+10z=-z+10 | | -5x(x+1)+3x-3=-14 | | 5=g8.g= | | (5x)(7x-13)(10x-5)=180 | | 8m+13m=63 | | ½(6t-4)=3t-2 | | 2^4=((x^2)+1)/(x-3) | | -9q+2=8-10q | | -3=-3+v/5 | | -5x+1+3x-3=-14 | | 23-15x=82 | | 3(-2x+1)=-1(2x+1 | | -4(2-x)=4/5(x+26) | | 9c=c-8 | | 2g-2g+3g=12 | | x3-7x2+15x-14=0 | | ŷ=0.375x+1.33 | | 4x-20+2x+20=180 | | -3k+9=7-4k | | 3x-52x=4 | | 6w+5w=-11 | | 4x+15=105 | | 8f-10=-2f | | 3+4(2-x)=3x | | 10=3+b/2b= | | -6+1=-2x+-1 | | 2d-d=15 | | 2+8b=122 | | 20d-19d=11 | | x-x^2=49/16 | | -75-k=-95K= |

Equations solver categories